The New Testament in its world : an introduction to the history, literature, and theology of the first Christians - Wright, N. T. (Nicholas Thomas); Bird, Michael F. (London: SPCK, 2015)
"The New Testament in Its World brings together decades of ground-breaking research, writing, and teaching into one volume that will open readers' eyes to the larger world of the New Testament. It presents the New Testament books as historical, literary, and social phenomena located in the world of Second Temple Judaism, amidst Greco-Roman politics and culture, and within early Christianity. "--
Includes bibliographical references (pages 891-923) and indexes.
Keywords: Bible. -- Introductions; Bible. -- Geography